Idaho [videorecording (DVD)] - Watt, Jim, 1943-; Noren, Sterling (Discoveries-- America., 2007)
Explore Koompin Bros. potatoes, Ketchum/Sun Valley, Trailing of the Sheep festival, Silver Creek fly fishing, Idaho National Laboratory, Craters of the Moon National Monument, Hyde driftboats, Henry's Fork Foundation, Teton Dam Museum, Hell's Canyon mail boat, and much more.